Learning Management Of Certified Teachers In Improving The Quality Of Student Religiosity At SMP Negeri Arun - Elvi Marfinda; Almuhajir (Universitas Djuanda, 2023)
This study aims to explain the learning management of certified teachers from the stages of planning, implementation, evaluation and follow-up of learning in improving the quality of student religiosity at SMP Negeri Arun. This research is a qualitative study using a descriptive approach. Data sources consist of primary data and secondary data. To obtain accurate data, researchers conducted three data collection techniques, namely observation, interviews, and documentation, while data analysis techniques consisted of data collection, data condensation, data presentation and drawing conclusions. The results showed that: 1) The learning planning of certified teachers in improving the quality of student religiosity at SMP Negeri Arun is carried out in accordance with the Regulation of the Minister of Education and Culture Number 22 of 2016, teacher planning documents are prepared by paying attention to student development areas such as encouraging students to participate actively, creatively, independently and with character, and planning concentrates on character building and Islamic culture, 2) The implementation of certified teachers' learning in improving the quality of student religiosity at SMP Negeri Arun varies by using an interactive learning approach with students and religiosity-integrated learning through development areas tailored to learning materials and activities, 3) Evaluation and follow-up of certification teachers' learning in improving the quality of student religiosity SMP Negeri Arun is in accordance with the applicable educational assessment standards in the Regulation of the Minister of Education and Culture Number 21 of 2022. Learning evaluation is carried out to determine the success of learning through the stages of collecting and processing information that can help teachers know student learning outcomes. Indicators of learning success are determined from the results of evaluation of both aspects of attitude, knowledge and skills.